2014
DOI: 10.5935/0103-507x.20140003
|View full text |Cite
|
Sign up to set email alerts
|

Augmented renal clearance in critically ill patients: incidence, associated factors and effects on vancomycin treatment

Abstract: ObjectiveAn augmented renal clearance has been described in some groups of critically ill patients, and it might induce sub-optimal concentrations of drugs eliminated by glomerular filtration, mainly antibiotics. Studies on its occurrence and determinants are lacking. Our goals were to determine the incidence and associated factors of augmented renal clearance and the effects on vancomycin concentrations and dosing in a series of intensive care unit patients.MethodsWe prospectively studied 363 patients admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 34 publications
6
80
0
1
Order By: Relevance
“…In a previous trial of febrile neutropenic patients, we observed that 31% of the study cohort exhibited ARC. This is comparable to other reports for intensive care unit (ICU) patients: 33% by Ruiz et al (26), 38.7% by Kawano et al (27), and 28% by Campassi et al (28). A higher incidence in ICU patients was also reported by other authors, e.g., 55.8% (29) and 65.1% (30).…”
Section: Discussionsupporting
confidence: 88%
“…In a previous trial of febrile neutropenic patients, we observed that 31% of the study cohort exhibited ARC. This is comparable to other reports for intensive care unit (ICU) patients: 33% by Ruiz et al (26), 38.7% by Kawano et al (27), and 28% by Campassi et al (28). A higher incidence in ICU patients was also reported by other authors, e.g., 55.8% (29) and 65.1% (30).…”
Section: Discussionsupporting
confidence: 88%
“…Minkut et al [16] showed that the risk of sub-optimal vancomycin exposure could be doubled in patients with ARC. Other recent studies have also shown that patients with ARC exhibit low vancomycin concentrations and require increased dosing for optimal exposure [11,30].…”
Section: The Influence Of Arc On Antibiotic Therapymentioning
confidence: 98%
“…As quantifying drug clearance is typically not routine, most literature considers ARC in terms of surrogate measures of GFR. In particular, a measured urinary creatinine clearance (CL CR ) > 130 mL/min/173 m 2 has often been employed as a threshold [2,5 ,9,10]; although lower [6,11] or higher [12] GFR cut-off points have also been used. Although this definition logically reflects the potential increase in clearance for those drugs that are primarily eliminated through glomerular filtration, it may not explain any contribution from altered tubular secretion or re-absorption, which is generally more difficult to assess.…”
Section: Defining Arcmentioning
confidence: 99%
“…Physiologic changes in the critically ill, such as increased cardiac output and enhanced blood flow to major organs, increase kidney perfusion, which can lead to ARC and higher clearance of renally eliminated medications. One group hypothesized that ARC is the natural response to critical illness in patients with a greater physiologic reserve, which is activated during states of stress. Severe trauma, infection, inflammation, burns, surgery, and pancreatitis can all potentiate a systemic inflammatory response syndrome, which results in increased cardiac output and capillary permeability, both of which lead to amplified renal blood flow and increased clearance of hydrophilic medications .…”
Section: General Mechanism Of Arcmentioning
confidence: 99%